ANALISIS KEMAMPUAN DAERAH, TINGKAT KEMANDIRIAN DAN EFEKTIVITAS REALISASI ANGGARAN PEMERINTAH KOTA TANGERANG TAHUN ANGGARAN 2010-2014 - DWI ANGGRAINI, RIRIS (Jurnal Akuntansi AKUNESA, 2015)
The ability of local and regional financial performance is measured using the ratio of DOF (Degree of Fiscal Autonomy), the ratio of IKR (Capability Index Routine), self-sufficiency ratio, and the ratio of PAD effectiveness. Judging from Tangerang City local financial capacity is considered quite able to implement regional autonomy. Besides the government's financial performance showed positive results. Tangerang City Government capable of realizing revenue in accordance with the targets set, even able to exceed the target, with an average ratio of 120.32%, which can be said to be effective. While the measurement using the ratio of self-sufficiency has not shown good results. On average during the five years the level of independence of Tangerang City still stands at below 50%, which means that the level of dependence on the central government through balancing funds, and other legitimate income areas is still quite high. But with these numbers form a pattern of relationships which means the consultative role of the central government has begun to diminish albeit slightly and is considered capable enough to implement regional autonomy.Keywords : Ability Regions, Regions Financial Performance, DOF ratio (Degree of Fiscal Autonomy), IKR Ratio (Capability Index Routine), self-sufficiency ratio, ratio of PAD effectiveness.